Ambidextrous leadership strategy in facing the VUCA era: a systematic literature review and its implications for state-owned telecommunications enterprises - Arief Hamdani Gunawan; Edi Istiyono; Widihastuti Widihastuti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The telecommunications industry is currently facing dual challenges in the VUCA era (Volatility, Uncertainty, Complexity, Ambiguity). Incumbent companies, particularly state-owned enterprises such as PT Telkom, are required to balance the exploitation of their core business for short-term profitability with the exploration of digital innovations for long-term sustainability. Objective: This study aims to analyze the concept of Ambidextrous Leadership as a key capability for senior leaders in navigating this innovation paradox and to formulate a conceptual framework for its application within state-owned enterprises. Method: The research employs a Systematic Literature Review (SLR) approach guided by the PRISMA protocol. Articles were collected from reputable databases (Scopus, Google Scholar) over the past ten years using keywords related to ambidextrous leadership and digital transformation. Results: The findings indicate that Ambidextrous Leadership consists of two dynamic behaviors: opening behavior (encouraging risk-taking and variance) and closing behavior (emphasizing efficiency and target achievement). In the bureaucratic context of state-owned enterprises, leaders require high cognitive flexibility to switch between these two modes. Conclusion: The implementation of Ambidextrous Leadership in the telecommunications sector necessitates an organizational culture that tolerates failure during the exploration phase while maintaining discipline during the exploitation phase.